PENGARUH PERBEDAAN KONSENTRASI LARUTAN ASAM ASETAT (CH3COOH) TERHADAP KARAKTERISTIK GELATIN KULIT KAKI AYAM - Pantow, Indri M.; Sompie, Meity; Mirah, Arie Dp.; Karisoh, Linda Ch. M. (Universitas Sam Ratulangi, 2016)
THE EFFECT OF ACETIC ACID CONCENTRATION ON CHARACTERISTICS OF CHICKEN LEG SKIN GELATIN. This research was aimed to determine the effect of differenceacetic acid (CH3COOH) concentration on chicken legs skin gelatin. The experiment were determined by analysis of Completely Randomized Design with one factors and five replicates of treatments.The factor was concentration of acetic acid solution consisting 4 level (1, 3, 5 and 7%).The results showed that the difference concentration acetic acid solution had high significant effect (P<0.01) on the the yields, viscosity, gel strength and pH value ofchicken legs skin gelatin.Yield of chicken legskin gelatin was13.57 to 15.49%, viscocity was ranged between 4.30 to 5.76, gel strength was 61.15 to 68.29 g Bloom and pH value was 5.24 to 5.58. The conclusion of this research was the chicken leg skin gelatin using acetic acid solution concentration 1 % to 7 % had the similar characteristics with the commercial gelatin and includedyields, viscosity, gel strength and pH value of Indonesian National Standard gelatin. Key words : Acetic acid, Gelatin and Chicken legs skin